Representasi Aspek Keterampilan Proses Sains pada Buku Teks Biologi SMA Materi Ekosistem - Rizqya Laylan Adha; Ummi Nur Afinni Dwi Jayanti (Universitas Muhammadiyah Prof. Dr. Hamka, 2022)
Background: Science Process Skills (SPS) is a skill that facilitates students to find realities, decide on ideas and apply theory to daily existence. Textbooks in North Sumatra are assorted, and the availability of SPS aspects is not widely known. This study aims to determine the availability of SPS aspects in the most widely used high school textbooks in senior high school in one of city in North Sumatera. Methods: This study used content analysis research. The samples were purposive sampling using the most widely used books in state high schools in Binjai City. The data analysis technique in this study includes quantitative and qualitative. Qualitative data analysis was carried out by identifying the emergence of SPS aspects in the analyzed textbooks. Meanwhile, quantitative data analysis is carried out by calculating the frequency and Percentage of occurrences of SPS aspects in biology textbooks. Results: The results showed that the high school biology textbook class 10 was appropriate in providing aspects of science process skills in Ecosystem material. Book A provides 80% of all aspects of science process skills and book B provides 60% of all aspects of observed science process skills. Conclusions: of this study can be used as a reference for teachers in choosing textbooks that will be used as learning resources in facilitating SPS. Furthermore, continuous efforts are needed from the government,